African animal trypanocide resistance: A systematic review and meta-analysis - Keneth, Iceland Kasozi; Ewan, Thomas MacLeod; Susan, Christina Welburn (2024)
African animals resistance ( AATr) continues to undermine global efforts to eliminate the transmission of africa intrypanosomiasis in endemic communities. the continued lack of new trypanocides has participated drug misuse and over use, thus contributing to the devlopment of the AADr phenotype. in this study, we investigated the threate associated with AAtr by using the major globally available chemotherapeutic agents. Methods: A total of seven electronic databases were screened for an article on trypanocide resistance in AATr by using keywords on preclinical and clinical trials with the number of animals with treatment relapse, days taken to relapse, and resistant gene markers using the PRISMA checklist. Data were cleaned using the SR deduplicator and covidence and analyzed using Cochrane RevMan®. Dichotomous outputs were presented using risk ratio (RR), while continuous data were presented using the standardized mean difference (SMD) at a 95% confidence interval. Results: A total of eight publications in which diminazene aceturate (DA), isometamidium chloride (ISM), and homidium chloride/bromide (HB) were identified as the major trypanocides were used. In all preclinical studies, the development of resistance was in the order of HB > ISM > DA. DA vs. ISM (SMD = 0.15, 95% CI: −0.54, 0.83; I 2 = 46%, P = 0.05), DA vs. HB (SMD = 0.96, 95% CI: 0.47, 1.45; I 2 = 0%, P = 0.86), and HB vs. ISM (SMD = −0.41, 95% CI: −0.96, 0.14; I2 = 5%, P = 0.38) showed multiple cross-resistance. Clinical studies also showed evidence of multi-drug resistance on DA and ISM (RR = 1.01, 95% CI: 0.71–1.43; I2 = 46%, P = 0.16). To address resistance, most preclinical studies increased the dosage and the treatment time, and this failed to improve the patient’s prognosis. Major markers of resistance explored include TbAT1, P1/P2 transporters, folate transporters, such as F-I, F-II, F-III, and polyamine biosynthesis inhibitors. In addition, immunosuppressed hosts favor the development of AATr.